2011
DOI: 10.1093/ejo/cjr008
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of four different computerized cephalometric analysis programs

Abstract: The aim of this investigation was to compare the traditional method of manual cephalometric tracing with four different computerized tracing programs, where the lateral cephalograms were scanned at 300 dpi and digitized onscreen. Thirty randomly selected cephalometric radiographs were used in this study. Four programs Dolphin Imaging, Vistadent, Nemoceph, and Quick Ceph were evaluated. Three dental, 11 skeletal, and 1 soft tissue parameters were measured that consisted of 5 linear and 10 angular measurements. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 12 publications
0
43
1
2
Order By: Relevance
“…Other authors have compared different software among them and observed similar results. Erkan et al 8 compared Dolphin ® , Vistadent ® , Nemoceph ® and Ceph Quick ® software, and did not find statistically significant difference among them. In the study of Vasconcelos et al 6 , Radiocef ® was compared to Dental Planner ® , but also no statistically significant difference was found.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other authors have compared different software among them and observed similar results. Erkan et al 8 compared Dolphin ® , Vistadent ® , Nemoceph ® and Ceph Quick ® software, and did not find statistically significant difference among them. In the study of Vasconcelos et al 6 , Radiocef ® was compared to Dental Planner ® , but also no statistically significant difference was found.…”
Section: Discussionmentioning
confidence: 97%
“…Within the field of Orthodontics, one should highlight computerized cephalometric tracing obtained with the aid of software, which has been becoming even more present in scientific studies and in clinical practice [5][6]8 .…”
Section: Discussionmentioning
confidence: 99%
“…Digital tracings were performed using NemoCeph NX 2009 for Windows (Nemotec, Madrid, Spain) 8 and SmileCeph for iPad (Glace Software, Imola, Italy). Before entering the landmarks, cephalograms were calibrated by digitizing two points on the length-measuring gauge within the digital cassette.…”
Section: Methodsmentioning
confidence: 99%
“…In computerized cephalometric analysis, once the requested landmarks have been entered, the software automatically calculates distances and angles, thus eliminating errors that may occur in hand tracing when drawing lines with a ruler and measuring angles with a protractor. 5,7,8 Furthermore, collecting computer-assisted cephalometrics is less time-consuming than manual tracing, 3,9 and it allows the user to obtain several analyses at a time. 6 In addition, digital archiving overcomes the problem of film deterioration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation